Analysis of User’s Comfort on Automated Vehicle Riding Simulation using Subjective and Objective Measurements - Muhammad Nur Aliff Mohd Norzam; Juffrizal Karjanto; Nidzamuddin Md. Yusof; Muhammad Zahir Hassan; Abd Fathul Hakim Zulkifli; Ahmad Azad Ab Rashid (Universitas Muhammadiyah Magelang, 2022)
The naturalistic study investigated the potential influence of personal driving preferences (assertive and defensive driving style) on users; comfort when being driven in an automated vehicle with a defensive driving style. Adopted the Wizard of Oz design, the study involved three phases: pre-, during, and post-driven to measure their comfort, perceived safety, and likeness as well as motion sickness propensity through self-report questionnaire and heart rate variation. After answering a set of questionnaires, participants were exposed to simulated driving in an automated vehicle with a defensive driving style. A statistical analysis produced no statistically significant difference between assertive and defensive participants. This indicates an overall preference, perceived comfort without severe motion sickness propensity to the defensive driving style of the autonomous vehicle, regardless of participants’ personal driving styles.